2019
DOI: 10.1094/pdis-07-18-1214-re
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sensitivity and Control Efficacy of Pyraclostrobin Against Botryosphaeria dothidea Isolates in China

Abstract: Botryosphaeria dothidea is an important fungal pathogen that causes apple ring rot, which can significantly reduce apple yield. Fungicide applications are the main control measure of apple ring rot worldwide. Pyraclostrobin is a quinone outside inhibitor (QoI) fungicide that has yet to be registered for control of B. dothidea in China. Baseline sensitivity of B. dothidea to pyraclostrobin (EC50 of mycelial growth inhibition) was assessed for 97 isolates collected in Shandong Province. The EC50 values ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, it is vulnerable to some diseases of early blight, gray mold, powdery mildew, and which seriously affect the yield and quality of wax gourd (Jiang et al, 2018). Pyraclostrobin has a good control effect on powdery mildew, gray mildew, downy mildew and other diseases (Bowness et al, 2016;Chen et al, 2012;Fan et al, 2019;Skandalis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is vulnerable to some diseases of early blight, gray mold, powdery mildew, and which seriously affect the yield and quality of wax gourd (Jiang et al, 2018). Pyraclostrobin has a good control effect on powdery mildew, gray mildew, downy mildew and other diseases (Bowness et al, 2016;Chen et al, 2012;Fan et al, 2019;Skandalis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the major commercial cultivars like red fuji, golden delicious, gala, and red delicious are highly susceptible to B. dothidea (Guan et al, 2015). Therefore, fungicide application is still the primary method to control apple ring rot worldwide (Fan et al, 2016(Fan et al, , 2019. Previous studies showed that synthetic fungicides including fludioxonil, fluazinam, pyrisoxazole (Song et al, 2018), difenoconazole, tebuconazole, prochloraz, trifloxystrobin (Dai et al, 2017), tebuconazole (Fan et al, 2016), and pyraclostrobin (Fan et al, 2019) exhibit great potential for inhibiting the apple ring rot.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fungicide application is still the primary method to control apple ring rot worldwide (Fan et al, 2016(Fan et al, , 2019. Previous studies showed that synthetic fungicides including fludioxonil, fluazinam, pyrisoxazole (Song et al, 2018), difenoconazole, tebuconazole, prochloraz, trifloxystrobin (Dai et al, 2017), tebuconazole (Fan et al, 2016), and pyraclostrobin (Fan et al, 2019) exhibit great potential for inhibiting the apple ring rot. However, the overuse of synthetic chemical pesticides leads to the development of fungicide resistance and causes environmental pollution and health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemical fungicides are still the primary strategies for controlling apple ring rot disease ( Dai et al, 2017 ; Song et al, 2018 ; Fan et al, 2019 ). However, these fungicides were potentially hazardous to human health, other non-target organisms, and the natural environment.…”
Section: Introductionmentioning
confidence: 99%